Immunomodulatory Synthetic Glycocluster Molecule Prevents Melanoma Growth in vivo - Honkanen, Meija; Narvi, Elli; Ojala, Veera; Jokilammi, Anne; Rantakari, Pia; Kronqvist, Pauliina; Kähäri, Veli-Matti; Veräjänkorva, Esko; Kurppa; Kari J; Rahkila, Jani; Ekambaram, Ramesh; et al. (John Wiley & Sons, 2025)
Triacedimannose (TADM) is a synthetic trivalent acetylated glycocluster and a transmembrane macrophage activator independent of the mannose receptor. TADM induces Th1-type immune responses and suppresses Th2-type cytokines in acute and chronic allergic inflammation models in vivo. We, therefore, wanted to test whether TADM could also facilitate anti-tumour tissue responses similar to what has been observed for the immune checkpoint inhibitors, such as anti-PD-1 and anti-CTLA-4. A syngeneic mouse melanoma model was selected since metastatic melanoma has been successfully targeted by checkpoint inhibitors in the clinic. TADM inhibited the growth of B16 mouse melanoma tumours at levels comparable to an anti-PD-1 antibody. TADM-treated tumours encompassed significantly more apoptotic cells as measured by TUNEL staining, and interferon-gamma (IFN-γ) expression was increased in the spleens of TADM-treated mice compared to untreated controls. TADM-treated mice also demonstrated increased Ly6 C low monocytes and neutrophils in the spleens. However, TADM-treated tumours showed no discernible differences in infiltrating immune cells. TADM can alone suppress the growth of melanoma tumours. TADM likely activates M1 type macrophages, type N1 neutrophils, and CD8+ and Th1 T cells, suppressing the type 2 immune response milieu of melanoma tumour with a strong type 1 immune response.